2023
DOI: 10.1371/journal.pone.0273037
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2, 3-dioxygenase is responsible for low stress tolerance after intracerebral hemorrhage

Abstract: In the chronic phase after intracerebral hemorrhage (ICH), the aftereffect-associated lowering of motivation burdens many patients; however, the pathogenic mechanism is unclear. Here, we revealed for the first time that indoleamine 2, 3-dioxygenase (IDO) expression and enzyme activity are increased in the collagenase-induced murine ICH model. IDO is a rate-limiting enzyme situated at the beginning of the kynurenine pathway and converts tryptophan, a source of serotonin (5-hydroxytryptamine; 5-HT), to kynurenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Previously, Honsi and colleagues (2008) reported time-course upregulated hippocampal IDO expression in mice models of cerebral ischaemia 72 h after the BCCAL [46]. Meanwhile, several studies identified that IDO is upregulated in acute and chronic phases of cerebral ischaemia and chronic brain damage after stroke injury [35,47,48]. Although our study did not suggest memory deficit in CCH rats, increased IDO was associated with poststroke cognitive impairment, depression, and mortality [47,49].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Previously, Honsi and colleagues (2008) reported time-course upregulated hippocampal IDO expression in mice models of cerebral ischaemia 72 h after the BCCAL [46]. Meanwhile, several studies identified that IDO is upregulated in acute and chronic phases of cerebral ischaemia and chronic brain damage after stroke injury [35,47,48]. Although our study did not suggest memory deficit in CCH rats, increased IDO was associated with poststroke cognitive impairment, depression, and mortality [47,49].…”
Section: Discussioncontrasting
confidence: 55%
“…This condition increases the susceptibility of the microglia to a secondary stimulus and exhibits an exaggerated inflammatory response. Uniquely, under the influence of cytokines, 'primed' microglia express heightened IDO levels, which serve immunoregulatory and tolerogenic functions [34][35][36]. Increased expression of IDO enhances amino acid tryptophan (TRP) degradation via the kynurenine pathway (KP), which can affect the host immune system and CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous ligands, such as 2, 3, 7, 8tetrachlorodibenzo-p-dioxin (TCDD) and various viruses, can activate the AhR signaling pathway in host cells (3)(4)(5). Endogenous AhR ligands, such as Kynurenine (Kyn) and arachidonic acid, induce the translocation of AhR from the cytoplasmic matrix to the nucleus, thereby regulating the transcription of various target genes (6). Activation of AhR leads to the upregulation of cytochrome P450 enzymes, including CYP1A1 and CYP1B1, which play a crucial role in facilitating detoxification and drug metabolism (2).…”
Section: Introductionmentioning
confidence: 99%